ChemInform Abstract: A Flexible Strategy Towards Thienyl‐, Oxazolyl‐ and Pyridyl‐Fused Fluorenones. Issue 50 (10th December 2013) - Souibgui, Amel; Gaucher, Anne; Marrot, Jerome; Aloui, Faouzi; Mahuteau‐Betzer, Florence; Ben Hassine, Bechir; Prim, Damien
Abstract Compounds (VII) and (VIII) are prepared by the same sequence consisting of heterocycle formation, Suzuki coupling and ring closure.